No increase of calcitonin gene-related peptide in jugular blood during migraine - Tvedskov, Jesper Filtenborg; Lipka, Kerstin; Ashina, Messoud; Iversen, Helle K.; Schifter, Søren; Olesen, Jes (Annals of neurology, 2005)
Increased calcitonin gene–related peptide (CGRP) in external jugular venous blood during migraine attack is one of the most cited findings in the headache literature. The finding has not been convincingly reproduced and is based on comparison with historic control subjects. The validity of this finding is important for the understanding of migraine. We therefore investigated the issue using an intrapatient comparison design and two different CGRP assays. We sampled blood from the external jugular and cubital vein during, as well as outside of, an attack of migraine without aura. We succeeded in 17 patients, whereas only cubital fossa blood could be sampled in an additional 4 patients. CGRP was measured with the same assay as most previous studies (assay I) and furthermore with a more sensitive and validated assay (assay II). For assay I, mean CGRP concentration in external jugular venous blood during attack was 17.18pmol/L compared with 15.88pmol/L outside of attack. Mean difference was 1.81pmol/L (95% confidence interval [CI]: −2.88, 6.41; p = 0.44). In peripheral blood during attack, CGRP was 16.86pmol/L compared with 17.57pmol/L outside of attack. Mean difference was −0.79pmol/L (95% CI: −4.64, 3.06; p = 0.69). For assay II, external jugular venous blood concentration of CGRP during attack was 32.59pmol/L compared with 30.59pmol/L outside of attack; mean difference was 2.00pmol/L (standard error, 2.39; 95% CI: −3.07, 7.07; p = 0.416). In peripheral blood during attack, CGRP was 33.37pmol/L compared with 31.84pmol/L outside of attack; mean difference was 1.53pmol/L (standard error, 1.90; 95% CI: −2.46, 5.51; p = 0.431). Thus, no difference between CGRP level in external jugular or cubital fossa blood during and outside of attack was found. No difference was found between external jugular and peripheral venous blood. Thus, previous findings of increased CGRP level in external jugular or cubital fossa venous blood could not be confirmed. Our finding strongly suggests that CGRP is not increased in jugular venous blood during migraine without aura. CGRP cannot be used as a biomarker to validate human or animal models of migraine. Ann Neurol 2005;58:561–568